Effect of Sodium Periodate on the Adsorption Capacity of Silica-Lignin from Rice Husk on Chromium(VI) - Yati B. Yuliyati; Solihudin Solihudin; Atiek Rostika Noviyanti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Reactive groups such as silanol, hydroxyl, and carbonyl groups in silica-lignin composites play a role in binding to chromium(VI) ions. The activation of functional groups in silica-lignin can be increased by the addition of an activator such as sodium periodate, which can also oxidize the lignin monomer (guaiasil) to ortho-quinone. This study aimed to obtain silica-lignin composites from rice husks activated by sodium periodate with a high surface area. Composite absorption was tested on chromium(VI) adsorption. Silica-lignin isolation was carried out by using the sol-gel method at concentrations of sodium hydroxide 5, 10, 15, and 20% (b/b). Silica-lignin activated with sodium periodate 10% (b/b) had the smallest particle size of about 8μm, with a surface area of 14.0888 m2.g-1 and followed Halsey isotherm adsorption model, with an adsorption capacity of 0.3054 mg.g-1.